From herbicide to flame retardant: The lamellar-like phosphorus-bridged amitrole toward high fire safety epoxy resin with light smoke and low toxicity. (March 2022) - Ai, Yuan-Fang; Liu, Xin-Duo; Bai, Wei-Bin; Lin, Yu-Cai; Xie, Rong-Rong; Jian, Rong-Kun
Abstract: In an attempt to alleviate the harmful impact of the flammability of epoxy resin on the environment, amitrole, a herbicide, has been converted to a novel flame retardant (PBA) with lamellar morphology through organophosphorus modification. This material has been utilized to fabricate fire safe epoxy thermosets (EP). EP containing 7.5 wt% PBA undergoes quick self-extinguishment upon ignition. This blend displays a high limiting oxygen index (LOI) value of 34%. More importantly, hazardous products (heat, smoke, toxic gases including CO/CO2 ) released during combustion of EP, are strongly suppressed in the presence of PBA. The mechanical properties of EP-PBA blends are comparable to those of virgin EP. The tensile strength of EP containing PBA is 90% of that of unmodified EP. The flexural strength of PBA blends is somewhat greater than that for EP containing no additive. A tactful strategy for the transformation of amitrole, a potential environmental contaminant to a benign flame retardant for polymers has been developed. Graphical abstract: Image 1 Highlights: A lamellar-like phosphorus-bridged amitrole (PBA) was prepared. The PBA exhibited excellent flame retardancy for epoxy resin. The flame-retardant mechanism of pyrolysis products was analyzed. The mechanical properties of EP-PBA materials were comparable to virgin EP.